Optimalisasi Strategi Marketing UMKM Desa Sukoreno Kecamatan Umbulsari Kabupaten Jember - Ferdiansyah Putra Manggala; Karina Nine Amalia; Stefani Felisia Irawan; Angelia Margaretha (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2024)
Sukoreno Village, Umbulsari District, Jember Regency, has great potential in the development of Micro, Small and Medium Enterprises (MSMEs). However, limitations in marketing and the use of digital technology are major challenges. The University of Jember's MSIB Thematic Community Service Program (KKN) seeks to address these issues through training in digital marketing and the use of e-commerce platforms. The methods used include field observation and literature analysis, followed by workshops covering marketing strategy theory, marketplace account creation, and hands-on demonstrations. Results showed an increase in MSMEs' understanding and skills in digital marketing, as well as an expansion of product marketing reach. Students also participated in local promotional activities and the creation of a village profile video, which contributed to the re-branding and positive image enhancement of Sukoreno Village. This activity succeeded in increasing the income of MSMEs, strengthening the relationship between students and the community, and promoting the potential of the village at large.